I-SCEM (Indonesia Song Culture Education Mobile) Sebagai Media Pembelajaran Pengenalan Lagu Daerah Indonesia: I-SCEM (Indonesian Song Culture Education Mobile) As a Learning Media for the Introduction of Indonesian Regional Songs - Kreswanto, Fendi Nur (Pedagogia : Jurnal Pendidikan, 2018)
The aim of this research is to find out the appropriateness and effectiveness of instructional media I-SCEM (Indonesia Song Culture Education Mobile) as Indonesian local songs recognition media. The method used in this research is quasi experimental design with one group pre-test - post-test pattern. The population is the whole students of Sendangmulyo 04 Semarang Elementary School and the sample is 91 V grade students of Sendangmulyo 04 Semarang Elementary School. The data was collected using test, data analysis with descriptive statistics technique and the measuring analysis with score gain analysis test. The results of material appropriateness and I-SCEM media is categorized as very feasible to be used in instructional purposes. Students’ mean score before using instructional media I-SCEM is 68,7, while after using the media is 78. Score improvement is 9,3 with score gain test is 0.46, it is categorized as medium interpretation. Based on the results of students’ learning and gain test, it can be concluded that using I-SCEM instructional media can improve students’ understanding of Indonesian local songs. Students are expected to be able to learn by themselves using I-SCEM instructional media. This research still needs further development especially in other cultural materials such as local cloths andhouses.